E-LKPD Based on Socio-Scientific Issues: A Means of Developing Science Literacy and Critical Thinking In The Era Of The Independent Curriculum - Sukmanah Chomsun; Dasrieny Pratiwi; Friska Octavia Rosa (Postgraduate, University of Mataram, 2025)
Against the background of the limitations of learning media in facilitating the learning needs of students, as well as the importance of critical thinking skills and science literacy in facing global challenges. The independent curriculum is an approach designed to meet the learning needs of students flexibly, but still requires the active role of teachers in conveying essential concepts, so the development of SSI-based e-LKPD is expected to be an effective learning innovation to develop students' critical thinking skills and science literacy. The purpose of the study is to measure the effectiveness of SSI-based e-LKPD on environmental pollution materials on students' science literacy and critical thinking. The use of the liveworksheet application is used for interactive learning media. This type of research is quasi-experimental design with the one group pretest-posttest design method. The research was conducted in grade VIII of junior high school in Tanggamus district with a total of 128 students. Data analysis uses n-gain test and t-test. The results of the analysis obtained an n-gain of 33 in the control class and 53 in the experimental class. This value is in the range of 40-55 with the category of less effective. Furthermore, the results of the t-test showed a significant difference between the control and experimental classes (p<0.05); reject H0, thus that SSI-based e-LKPD is effective in improving critical thinking skills and science literacy of junior high school students.